(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
This paper deals with possible impact of potential pulp mill in Jekabpils on adjacent regions infrastructure, which includes inhabitant’s comfort level, and business infrastructure during construction and processing stages. The analysis is made up on the basis of several publications, which are connected with environmental impact assessment, regional development and pulp mill project materials. There are analysis of several kinds of impact: on geology, water and air pollution and their limitation, noise pollution, demography, cultural resources. For better understanding of business perspectives a comparison is made with similar pulp mill in Rauma (Finland) and its impact. On this basis SWOT analysis and matrix is made. The main conclusions are: there is big possibility of positive changes in region development through so large investment, main problems in pollution are connected with possible thermal pollution, serious attention needs to be paid for future for small sawmill and private forest management.